Are serum and biliary carcinoembryonic antigen and carbohydrate antigen19-9 determinations reliable for differentiation between benign and malignant biliary disease? - Meral AKDOĞAN; Erkan PARLAK; Burçak KAYHAN; Mevhibe BALK; Gül ERSAVAŞTF; Burhan ŞAHİN (Turkish Journal of Gastroenterology, 2019)
-